2021
DOI: 10.1155/2021/1279359
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Bergapten against Human Erythrocyte Hemolysis and Protein Denaturation In Vitro

Abstract: Bergapten, a furocoumarin found in many medicinal plants, is used for the management of various conditions. The present in vitro study evaluated the ability of bergapten to prevent human erythrocyte hemolysis and protein denaturation. Bergapten administered at 10, 30, and 100 μg/ml exhibited a significant concentration-dependent protection on the erythrocyte membrane exposed to hypotonicity and heat-induced hemolysis. The concentration at which bergapten inhibited 50% of the cells from hemolysis (IC50) was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…For instance, the denaturation of tissue proteins results in the production of autoantigens in arthritis [27,28]. Membrane proteins regulate water/volume content of the cell controlling the movement of ions such as sodium and potassium via ion channels [29]. From the result in this study, it was shown that the ethanol extract of kiwano rind inhibited denaturation of bovine albumin treated with heat in a concentration-dependent manner exhibiting 47.14% maximum activity.…”
Section: Discussionmentioning
confidence: 80%
“…For instance, the denaturation of tissue proteins results in the production of autoantigens in arthritis [27,28]. Membrane proteins regulate water/volume content of the cell controlling the movement of ions such as sodium and potassium via ion channels [29]. From the result in this study, it was shown that the ethanol extract of kiwano rind inhibited denaturation of bovine albumin treated with heat in a concentration-dependent manner exhibiting 47.14% maximum activity.…”
Section: Discussionmentioning
confidence: 80%
“…The stability of the erythrocyte membrane can be extrapolated to the stabilization of the lysosomal membrane, due to its absence of organelles and similarity to the cell membrane [ 104 ]. During the inflammatory process, leukocytes and neutrophils release lysosomal enzymes towards the inflammation sites [ 105 , 106 ], and these can generate persistent inflammation and tissue damage, threatening human health. The osmosis effect of vascularization during inflammation is reproduced by the hypotonic solution, an analysis where the stabilization of the RBC membranes represents the lysosomal membranes, whose importance lies in limiting the inflammatory response by preventing the release of lysosomal enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…erefore, any agent that can prevent protein denaturation is worth considering for anti-inflammatory drug development. Most nonsteroidal anti-inflammatory drugs (NSAIDs) are known to possess the intrinsic ability to stabilize or prevent heat-treated albumin denaturation at physiological pH 6.2-6.5 [35,37]. Also, it has been reported that the administration of NSAIDs to overweight patients may improve the loss in their body weight [38].…”
Section: Discussionmentioning
confidence: 99%